FORMULASI KRIM HERBAL KULIT PISANG AGUNG SEMERU LUMAJANG TERHADAP Candida albicans dan Staphylococcus aureus - Dwi Nur Rikhma Sari; Septarini Dian Anitasari; Khoiriyah Khoiriyah (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Skin cream, is one of the dosage forms, which contain little water content, and is widely used both as a medicinal and cosmetic cream. This study made an herbal cream formulation based on Agung Semeru banana skin of Lumajang variety which was known as an antimicrobial at a concentration of 100% which would then be tested for its ability as an antimicrobial against the growth of Candida albicans and Staphylococcus aureus. The method used in this study is using the paper disk Diffusion method with 6 repetitions, where data in the form of inhibitory zone diameters were analyzed using 1% One Way ANOVA test and continued with Duncan's test at 1%. The results of this study showed that there were significant differences between the treatment groups (α = 0,000), where the cream formulation of the Candida albicans fungi showed a larger inhibition zone diameter (22.50 ± 1.70 mm) than the inhibitory zone diameter in Staphylococcus aureus bacteria (21 , 50 ± 1.68 mm).